Case study of roadway visibility at Hulu Langat - Ampang Road - Suhana , Sufian (2013)
Road accident is one of the crucial issues to be discussed currently. The reason is that it is increasing from years to years despite of many initiatives that had been by the government. This thesis deals with roadway visibility at Hulu Langat - Ampang road using several variable causal factors which related to the high number of accident at the road. The objectives of this thesis are to identify the road users' opinion about the road and also to determine the relationship between visibility and the number of accidents at the Hulu Langat - Ampang road. For the research, the information is gathered from Ampang Traffic Police Department and Kajang Municipal Council which is number of accidents and the road information. The road is dividing between several sections to detect which section is having the highest number of accidents. Besides, the thesis had uses questionnaire method and analysis by using SPSS software for the results analyzing. By using the questionnaire, the opinion of the road users' is known and conclusions were made based on several factors. Same goes for the/analyzing by using SPSS software, the correlation is obtained by considering some causal factors such as the lighting, safety aspect, signage, and condition of the dark road to number of accidents. The causal factors is being analyze whether it is having significant relationship to the number of accidents or vice versa. From the results, it is observed that lighting and condition of the dark road is shows significantly relationship to the number of accidents that happened at Hulu Langat- Ampang road. Therefore, the lighting and darkness of the road is giving big impact to the number of accidents happened and thus, from the results also, showing that the most critical section that having highest accident is section 4. Thus, the authority should play their role of the visibility improvement at Hulu Langat- Ampang road for the sake of road users' safety.